KETERAMPILAN DAN NILAI SEBAGAI MATERI PENDIDIKAN DALAM PERSPEKTIF ISLAM - Sudarto, Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
Educational goals will not be achieved as expected without equipping students with educational material. When the formulation of educational goals differ from one society to another, of course, the material needed to achieve that goal is also different. Educational material consists of three elements, namely knowledge, skills, and values. This is the reference in the following discussion. Starting from this premise, in the following discussion will be discussed matters related to the skills and values as educational material.By using literature study can be summarized as follows: First, the technical skill is the ability to perform an act. Urgency leads to the effectiveness and efficiency of a job. Second, the skills in the view of Islam is a necessity in the educational material. Third, is the quality or value of something. Each object or event in the universe has a certain quality. While the stuff consists of intrinsic value and instrumental value. Fourth, values that must be educational material in the view of Islam are values sourced and based al-Quran and al-Sunnah al-Nabawiyah. The main benchmark in setting the value of something is the second source of Islamic teachings. Cultural values are acceptable as long as not contrary to Islamic values.Â Keywords: skills, values and educational material